Assessment of Stunting Status and Stunting Prevention Efforts in Toddlers in Penajam District, North Penajam Paser Regency - Ruminem Ruminem; Mayusef Sukmana (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
North Penajam Paser Regency (PPU) is one of the 100 priority districts/cities for stunting intervention in Indonesia. The prevalence of stunting in PPU Regency is 27%, while the prevalence in East Kalimantan is 28.3%, and nationally, 36.4%. Stunting has an impact on impaired brain growth, physical growth, and development. The purpose of community service is to analyze the characteristics of stunting toddlers and stunting prevention through posyandu activities. The method of implementing descriptive-analytic through secondary data collection activities for stunted toddlers is described. Posyandu activities for toddlers through health checks, providing nutrition education to toddlers in the villages of Penajam, Gunung Steleng, Nipah Nipah, and Nenang. Literature study on the prevention of stunting under five by the local government of PPU Regency. The results showed that there were 92 stunting toddlers, 53 boys, and 39 girls, with 68 short toddlers and 24 very short toddlers, most of whom were >24 -60 months old, i.e. 59 toddlers. Stunting prevention includes health checks for children under five, education on stunting prevention at posyandu and strengthening of stunting prevention/control policies with Regent Regulations. More optimal efforts are needed in implementing the Regent's regulation for the prevention of stunting under five.